Variations in gynaecologists’ reasoning over a pelvic pain vignette: What does it tell us on empowering approaches? - Schwind, Bettina; Gross, Karin; Tschudin, Sibil; Wehner, Nina; Lagro-Janssen, Toine (My University, 2015)
This study aims to explore gynaecologists’ medical reasoning about pelvic pain management to understand what may underlie empowering approaches. 11 semi-structured interviews with physicians were conducted across 6 outpatient gynaecological settings within the Basel area, Switzerland. Analysis followed a constructive interpretative grounded theory approach according to Charmaz. Three emergent perspectives regarding patient empowerment were identified. They demonstrate how the complex socialisations of men and women as gynaecologists in their work environment affect their medical reasoning. While some perspectives hamper, others enable clinicians to take an empowering approach. Training courses in self-reflective approaches are recommended to support clinicians in developing and supporting an empowering approach towards patients with chronic pelvic pain and to go beyond a biomedical perspective.
Keywords: Gender; Beruf; Sozialisation; Gesundheit; 610 Medizin und Gesundheit; medizinische Argumentationsweise; Gynäkologie; Unterbauchschmerz; Schweiz